Sirolimus Add-On Rescue Therapy Can Benefit Patients with Chronic Renal Allograft Dysfunction - 蔡孟昆(Meng-Kun Tsai); 李志元(Chih-Yuan Lee); 胡瑞恆(Rey-Heng Hu); 李伯皇(Po-Huang Lee) (Journal of the Formosan Medical Association, 2003)
Nephrotoxicity caused by calcineurin inhibitors (CNIs) contributes to chronic renal allograft dysfunction (CRAD). This retrospective cohort study evaluated the immunosuppressive and nephrotoxic effects of sirolimus add-on therapy with minimization of CNI in patients with CRAD. Twenty patients with CRAD were recruited to receive sirolimus add-on rescue (SRL-AR) therapy. The SRL-AR therapy added 6 mg of sirolimus for loading and 2 mg/day for maintenance to CNI-based maintenance immunosuppressive regimens and reduced the dose of CNI, either cyclosporine or tacrolimus, by half at the initiation of sirolimus loading. The primary endpoint of the study was estimated glomerular filtration rate (GFR) determined using the Cockcroft-Gault formula. The efficacy of this SRL-AR therapy was evaluated by comparison to a historic group of 30 patients with CRAD who received a tacrolimus-based rescue therapy. Of the 20 patients receiving sirolimus therapy, 2 had graft failure during the 12-month follow-up. The post-rescue GFR values of the patients receiving sirolimus therapy showed greater improvement than those of the historic group during follow-up except for month 8, with the differences in GFR changes reaching significance at months 1 to 5 (p < 0.05). Multiple regression analysis identified graft age and GFR upon rescue in addition to the SRL-AR therapy as significant factors associated with post-rescue GFR changes. This study demonstrated that SRL-AR therapy combined with reduced CNI doses could effectively improve short-term renal function of patients with CRAD. The long-term outcome of rescuing CRAD is likely to depend on factors including graft age and GFR upon rescue.